Optimalisasi Digital Marketing Berbantuan E-Commerce Shopee untuk Pemberdayaan Ekonomi Kelompok Petani Bangunharjo Sragen - Dhany Efita Sari; Seli Fatmahwati; Vinna Idamatus Silmi; Kurniawan Ari Saputro (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2023)
In the era of disruption 4.0, so as not to be eroded by ongoing technological developments, it is necessary to apply and understand technology in promotional activities so that it can help increase turnover and business expansion, especially among economic actors. The mushroom farmer group in Dukuh Bangunharjo, Jirapan Village, Sragen is one of the economic actors that has potential and needs to be developed. The method used is to provide direct assistance in creating and managing Shopee e-commerce accounts. Assistance is carried out for five times mentoring. The results of this activity show that the Bangunharjo farmer group still lacks knowledge about digital marketing, especially the use of Shopee sellers. From the results of the assistance it is evident that the Bangunharjo farmer group already understands the use and management of Shopee e-commerce as a media for promotion and sales. In addition, the Bangunharjo farmer group felt an increase in their skills on how to use various features at Shopee. After this mentoring activity, it is hoped that follow-up activities will be needed with ongoing coaching in using digital marketing effectively and optimally so that it can support marketing activities and increase sales of the Bangunharjo farmer group business.Di era disrupsi 4.0 agar tidak tergerus oleh perkembangan teknologi yang sedang terjadi maka diperlukan penerapan dan pemahaman teknologi dalam kegiatan promosi agar mampu membantu untuk meningkatkan omset dan perluasan usaha terutama dikalangan pelaku ekonomi. Kelompok tani jamur Dukuh Bangunharjo, Desa Jirapan, Sragen adalah salah satu pelaku ekonomi yang memiiki potensi dan perlu dikembangkan. Metode yang digunakan yaitu dengan memberikan pendampingan langsung pembuatan dan pengelolaan akun e-commerce  Shopee. Pendampingan dilakukan selama lima kali pendampingan. Hasil dari kegiatan ini menunjukkan bahwa kelompok tani Bangunharjo masih minim pengethuan mengenai digital marketing terutama penggunaan Shopee seller. Dari hasil pendampingan terbukti bahwa kelompok tani Bangunharjo sudah memahami penggunaan dan pengelolaan e-commerce Shopee sebagai media promosi dan penjualan. Selain itu, kelompok tani Bangunharjo merasakan adanya peningkatan keterampilan tentang cara penggunaan berbagai fitur di Shopee. Setelah kegiatan pendampingan ini diharapkan perlunya kegiatan tindak lanjut dengan pembinaan berkelanjutan di dalam menggunakan pemasaran digital secara efektif dan optimal sehingga dapat mendukung kegiatan pemasaran dan meningkatkan penjualan usaha kelompok tani Bangunharjo.